Ameliorative effect of Vitis gracilis leaf decoction against sensory and motoric disorders, oxidative stress, and cerebellar degeneration in diabetic mice - Putra Santoso, Alfi Yuniarti, Rita Maliza, Alimuddin Tofrizal, Dinda Fadhila Belahusna (Journal of Applied Pharmaceutical Science, 2024)
Vitis gracilis (Vitaceae) is a potent medicinal plant, but its effectiveness in counteracting neuronal issues due to diabetes is uncertain. This study aimed to investigate whether the leaf decoction of V. gracilis could manage sensory and motoric disorders, oxidative stress, and cerebellar degeneration caused by diabetes mellitus. Twenty-five adult male mice were divided into five treatment groups: non-diabetic (non-DM), diabetic (alloxan-induced diabetes mellitus; DM), and DM treated with V. gracilis leaf decoction at doses of 25 g/l (DM + 25 g/l VgD), 50 g/l (DM + 50 g/l VgD), or 100 g/l (DM + 100 g/l VgD). The decoction was administered orally for 30 days. The results showed that V. gracilis leaf decoction did not significantly lower blood glucose levels or improve insulin tolerance in diabetic mice (p > 0.05). However, it substantially maintained sensory response and motoric balance and reduced malondialdehyde levels in brain tissue, especially at a 100 g/l dose (p < 0.05). Moreover, higher decoction doses alleviated histopathological alterations in the cerebellum by significantly preserving molecular and granular layer thickness while reducing degenerated Purkinje cells (p < 0.05). In conclusion, despite its inability to manage hyperglycemia, the decoction effectively improved sensory and motoric function, reduced oxidative stress, and mitigated cerebellar histopathological changes. Therefore, V. gracilis could be an alternative treatment for diabetes-related neurological disorders.
Keywords: Diabetes mellitus, malondialdehyde, neuropathy, oxidative stress, Purkinje cells